MODEL PEMBERDAYAAN MASYARAKAT DALAM RANGKA KONSERVASI LAHAN RAWAN BENCANA LONGSOR DI KECAMATAN JATIYOSO KABUPATEN KARANGANYAR - Wida R, Erlyna; Suminah, Suminah (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2011)
The topography of Jatiyoso sub-district is steep and mountainous, leading to potential erosion and landslide. Adding more problems to such situation, most farming activities tend to plant seasonal crops without any land conservation attempts. This research aimed to set up a model of community empowerment in landslide prone areas. Results showed that a successful program of community empowerment in landslide-prone areas must comprehensively involve every community elements. The community empowerment model was created based on input, process, and output. The end result of such empowerment model should hopefully generate community participation in the effort of land conservation in landslide prone areas.